Early Adult Psychosocial: Synthesizing Erick Erikson's Theory in Islamic Concepts - Faila Sufah; Eva Latipah; Ismatul Izzah (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
Human life is likened to a plant that will have developed in the phases of its life, one of which is early adulthood which will experience psychosocial development. This study aims to examine the psychosocial theory of early adulthood synthesizing Erik Erikson’s theory in Islamic concepts. The research method is library research using content analysis. The results showed that in the Islamic concept at this time humans enter the taklifi phase a have sexual maturity, obligations as 'Abdullah, and as caliphs on earth. Psychosocial in early adulthood experienced by humans in Erik Erikson's theory is intimacy versus isolation. Intimacy is a sexual development that leads to sexual relations with the opposite sex. When intimacy is not achieved, he will experience isolation, which is the tendency to avoid social interaction with others. In the Islamic concept, it is explained that in carrying out a relationship to achieve intimacy, humans must build communication with Allah SWT and their partners, understand the family background, habits, and psychology, and increase knowledge about the differences and needs between men and women so that isolation does not occur. Isolation is a disease in a person that can be overcome by increasing dhikr to Allah SWT.